Penerapan Metode Discoveri Untuk Meningkatkan Hasil Belajar IPA Siswa Kelas Iv SDN 020 Rambah Hilir Kabupaten Rokan Hulu - Ertahayati Ertahayati (STKIP Rokania Pasir Pangaraian, 2018)
This research is motivated by the existence of science learning problems. The result of science learning obtained by grade 4 students SDN 020 Kecamatan Rambah Hilir often under KKM, students often remedial, at the time of science practice many students who do not understand. The type of research is classroom action research with research procedure consisting of planning, action implementation, observation, and reflection. The results showed that there was an increase in science learning outcomes of grade 4 students of SDN 020 Kecamatan Rambah Hilir after applied discovery learning method. In the first cycle of science learning achievement achieved by students with an average value of 72.1. in the second cycle of learning achievement of science achieved by students increased to 75.3